Analysis and Practice of Cloud Computing Information Security - Detian Tong; Xudong Liu; Taofeng Guo; Jiewen Liang (Dianxin kexue, 2013)
Cloud computing security issue is one of the most important and difficult problems encountered in today’s cloud computing technology to promote 1anding.From the cloud computing security in the information security section，the basic content of information security in cloud computing and the current cloud computing were described；information security issues were analyzed；some of the solutions and the prospects of cloud computing were given. Fina11y，a brief discussion of GMCC private cloud platform cloud computing security practice was presented.